Dural arteriovenous fistulas with direct cortical venous drainage treated with Onyx®: a case series Fístulas arteriovenosas durais com drenagem cortical direta tratadas com Onyx®: casuística - Felipe Padovani Trivelato; Daniel Giansante Abud; Alexandre Cordeiro Ulhôa; Tiago de Jesus Menezes; Thiago Giansante Abud; Guilherme Seikem Nakiri; Benedicto Oscar Colli; Sebastião Nataniel Silva Gusmão; Marco Túlio Salles Rezende (Arquivos de Neuro-Psiquiatria)
Dural arteriovenous fistulas (DAVFs) may have aggressive symptoms, especially if there is direct cortical venous drainage. We report our preliminary experience in transarterial embolization of DAVFs with direct cortical venous drainage (CVR) using Onyx®. METHOD: Nine patients with DAVFs with direct cortical venous drainage were treated: eight type IV and one type III (Cognard). Treatment consisted of transarterial embolization using Onyx-18®. Immediate post treatment angiographies, clinical outcome and late follow-up angiographies were studied. RESULTS: Complete occlusion of the fistula was achieved in all patients with only one procedure and injection in only one arterial pedicle. On follow-up, eight patients became free from symptoms, one improved and no one deteriorated. Late angiographies showed no evidence of recurrent DAVF. CONCLUSION: We recommend that transarterial Onyx® embolization of DAVFs with direct cortical venous drainage be considered as a treatment option, while it showed to be feasible, safe and effective. As fistulas arteriovenosas durais (FAVDs) podem se manifestar com sintomas agressivos, especialmente se existe drenagem cortical direta. Relatamos nossa experiência preliminar na embolização transarterial de FAVDs com drenagem cortical direta usando Onyx®. MÉTODO: Nove pacientes com FAVDs com drenagem cortical direta foram tratados: oito do tipo IV e uma do tipo III (Cognard). O tratamento consistiu na embolização transarterial usando Onyx-18®. Angiografias imediatas pós-tratamento, evolução clínica e angiografias de controle tardias foram estudadas. RESULTADOS: A oclusão completa da fístula foi alcançada em todos pacientes através de um só procedimento e injeção em apenas um pedículo arterial. No seguimento, oito pacientes ficaram livres de sintomas, um melhorou e nenhum deteriorou. Angiografias tardias de controle não mostraram evidência de FAVD recorrente. CONCLUSÃO: Nós recomendamos que a embolização transarterial com Onyx® das FAVDs com drenagem cortical direta, seja considerada como uma opção terapêutica, uma vez que mostrou ser factível, segura e efetiva.